SOIL SHRINKAGE CURVES AND MICROMORPHOLOGY IN CONTRASTING MANAGEMENTS - Fernandez, Patricia Lilia; Alvarez, Carina Rosa; Behrends Kraemer, Filipe; Morrás, Héctor José María; Scheiner, Javier; Boivin, Pascal; Taboada, Miguel Angel (Ciencia del Suelo, 2020)
Compaction processes are generally described using methods that do not distinguish volume changes of different types and pore sizes. The adjustment of shrinkage curves (ShC) using the XP model allows elucidation of the effects of soil management on changes in pore volume. This method coupled with micromorphological and micromorphometric determinations in soil thin sections allows the characterization and quantification of important soil features included pore types. The aim of this work was to examine the potential of shrinkage analysis to describe soil physical degradation under the most common management (continuous cropping-CC), an alternative management (integrated crop/livestock-ICL), related to quasi-pristine (QP); in two soils of northern of the Pampean region of Argentina (Typic Hapludoll and Typic Argiudoll). We focused on the changes of soil structural porosity in both methods (ShC and micromorphological analyses) in silty soils with low shrinkage-swelling capacity. The QP had a higher volume (or lower bulk density) in both soils. The slope of the structural phase was QP<ICL<CC, indicating lower structural stability, as a consequence of macropore destruction due to management intensity. Micromorphological analyses were in concordance to shrinkage analysis. QP showed higher structural pores from shrinkage analyses; and from micromorphometric analyses: higher Pores>50 um, a good pore orientation (vertical angles), and crumb microstructure derived from an intense biological activity were observed. In Typic Hapludoll, structural porosity in CC and ICL presented similar values according to ShC determinations. In Typic Argiudoll CC it was presented a lower values of structural porosity than in ICL. Similar results were estimated from micromorphological analyses (Pores>50 µm = QP(20.0%)>ICL(17.7%)>CC(16.0%)). CC and ICL were characterized by the development of platy peds and horizontally oriented planes, whereas ICL presented more biological activity. ShC and micromorphology analyses improved the understanding of soil functioning in these non-expansive soils, allowing the comparison between cattle trampling and continuous cropping in different soil types.